Sexual dimorphism and reproductive biology of bronze featherback (Notopterus notopterus, Pallas 1769) from Kelekar River, Ogan Ilir, South Sumatra, Indonesia - Muslim Muslim; Mochamad Syaifudin; Ferdinand Hukama Taqwa; Muhammad Iqbal Saputra (مجلة بغداد للعلوم)
Sexual dimorphism and reproductive biology are fundamental aspects of fish breeding studies. The aim of this research was to analyze the sexual dimorphism and reproductive biology of Notopterus notopterus. A total of 74 N. notopterus were collected from the Kelekar River in Ogan Ilir Regency, Indonesia, consisting of 38 males (TL: 18–23.6 cm; BW: 35.1–92.1 g) and 36 females (TL: 19.6-26.3 cm; BW: 49.4–133.8 g). Seventeen morphometric characters, three meristic characters, and five reproductive biological parameters were analyzed. The results showed the differences in the morphometric characteristics of male and female N. notopterus. However, there was no difference in the meristic characters. The male gonadosomatic index ranged from 0.15 to 0.61%, and the female from 1.12 to 9.10%. The hepatosomatic index of males ranged from 0.19 to 1.38%, and that of females ranged from 0.15 to 1.23%, with a sex ratio of 1.056:1, fecundity of 1.007–3.901 eggs, ova diameters of 1.1–3.9 mm, and maturity levels of developed gonads to mature for males and mature to spawning for females. In conclusion, the differences between male and female N. notopterus can be identified morphologically.